2020
DOI: 10.1111/ctr.13777
|View full text |Cite
|
Sign up to set email alerts
|

Ureterostomy as an alternative to ileal conduits in pediatric kidney transplantation

Abstract: Introduction Urinary diversion in pediatric renal transplant candidates with bladders not amenable to primary reconstruction can be achieved by pre‐transplant ileal conduit creation. We performed cutaneous ureterostomies to limit pre‐transplant surgery, protect the peritoneum for dialysis, transplant patients sooner, and preserve ureter length for future surgical reconstruction. Methods We compared four pediatric transplant recipients with ureterostomies to four recipients with ileal conduits from 2009 to 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…They reported comparable creatinine clearance and UTI occurrence at 1 year in four children with ureterostomy formation compared to those with ileal conduits concluding that ureterostomy formation is safe and may be associated with a lower incidence of recurrent UTI. 11 Original reports suggested that ureterostomy formation at renal transplantation was associated with frequent complications-particularly stomal stenosis. 14,15 As the technique progressed, outcomes improved, although stomal stenosis and need for dilatation remain a concern.…”
Section: Ta B L E 1 Comparison Of Urinary Diversion Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…They reported comparable creatinine clearance and UTI occurrence at 1 year in four children with ureterostomy formation compared to those with ileal conduits concluding that ureterostomy formation is safe and may be associated with a lower incidence of recurrent UTI. 11 Original reports suggested that ureterostomy formation at renal transplantation was associated with frequent complications-particularly stomal stenosis. 14,15 As the technique progressed, outcomes improved, although stomal stenosis and need for dilatation remain a concern.…”
Section: Ta B L E 1 Comparison Of Urinary Diversion Proceduresmentioning
confidence: 99%
“…The formation of a cutaneous transplant ureterostomy is a relatively uncomplicated surgical procedure which has shown positive results, though to date most of the studies are in adults transplant recepients. 11,[14][15][16][17]21 This intervention can be performed as part of a single operative procedure at the time of transplantation in a select group of children with complex urological issues.…”
Section: Ta B L E 1 Comparison Of Urinary Diversion Proceduresmentioning
confidence: 99%
See 3 more Smart Citations